Dynamics and Proton Conduction of Heterogeneously Confined Imidazole in Porous Coordination Polymers. (18th January 2023) - Cai, Linkun; Yang, Junsheng; Lai, Yuyan; Liang, Yuling; Zhang, Rongchun; Gu, Cheng; Kitagawa, Susumu; Yin, Panchao
Abstract: The nanoconfinement of proton carrier molecules may contribute to the lowing of their proton dissociation energy. However, the free proton transportation does not occur as easily as in liquid due to the restricted molecular motion from surface attraction. To resolve the puzzle, herein, imidazole is confined in the channels of porous coordination polymers with tunable geometries, and their electric/structural relaxations are quantified. Imidazole confined in a square‐shape channels exhibits dynamics heterogeneity of core‐shell‐cylinder model. The core and shell layer possess faster and slower structural dynamics, respectively, when compared to the bulk imidazole. The dimensions and geometry of the nanochannels play an important role in both the shielding of the blocking effect from attractive surfaces and the frustration filling of the internal proton carrier molecules, ultimately contributing to the fast dynamics and enhanced proton conductivity. Abstract : Imidazole confined in porous coordination polymers' channels exhibits dynamics heterogeneity of typical core‐shell‐cylinder model, in which the core‐layer possess faster rotating dynamics contributing to enhanced proton conductivity.